Efektivitas Pengelolaan Anggaran Dana Desa dalam Pembangunan Infrastruktur di Desa Sileang Kabupaten Humbang Hasundutan Tahun 2021 - Rusli Roganda Sihite; Adam Adam; Walid Musthafa (Universitas Medan Area, 2023)
This research was conducted to see the effectiveness of managing the Village Fund Budget, namely to see an increase in village infrastructure development in Sileang Village, Doloksanggul District, Humbang Hasundutan Regency. Based on the problems studied, the method and type of research used descriptive qualitative research. Using data analysis techniques according to Miles and Huberman with interview data collection techniques and documentation, the key informants in this study were the village heads and the main informants were development heads and additional informants were four people from Sileang Village. The results of the research show that the management of the Village Fund Budget in the development of village infrastructure in 2021 has not been running effectively, it can be seen from the dimensions that are used as measuring instruments, there are still dimensions that are fully operational. Starting from the ineffective implementation of the planning coordination mechanism and funding system, the lack of budgetary resources owned by the village government so that the limited development programs implemented, the lack of maturity in terms of development planning, in the implementation of socialization the community involved must be limited due to the Covid-19 pandemic, there are still village officials who are not participatory in managing village funds, as well as facilities and infrastructure for infrastructure development in Sileang village are not yet adequate. Efforts that can be made to overcome obstacles and obstacles regarding the implementation of Sileang village government. The government should try to coordinate between regions/hamlets optimally so that unwanted problems do not occur, increase public awareness of development by actively participating in deliberations, and also conduct socialization of programs that have been formulated to the community so that people are more aware of the program.